Shakespeare and Feminism: Gender Politics in Antony and Cleopatra (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper examines Antony and Cleopatra from a feminist perspective, exploring the controversies that Cleopatra’s character has sparked among critics across different historical periods. Cleopatra exemplifies the fluidity and performativity of gender in ways that resist traditional definitions and expand gender boundaries. Most critics portray her as a captivating queen in a world dominated by patriarchs, while feminists view her not simply as a charming woman but also as a symbol of female rebellion. This paper investigates how the text subverts binary views of gender roles and challenges power structures and gender dynamics through a close examination of Cleopatra’s character in light of diverse feminist perspectives.